Evaluation of cardiovascular disease in the turner syndrome population in Northern Ireland. (3rd October 2022) - Kearney, A; MacElhatton, D; McManus, J; Muir, A
Abstract: Background: There is higher frequency of both congenital heart disease and acquired cardiovascular conditions in patients with Turner syndrome. It is associated with increased early morbidity and mortality compared with the general population related mainly to cardiovascular complications. Purpose: We sought to ascertain the prevalence and outcomes of cardiac abnormalities in patients with Turner syndrome in Northern Ireland. Methods: Patients with Turner Syndrome who attended cardiology or gynaecology clinics in the Belfast Health and Social Care Trust were identified and demographic and clinical data were obtained. Results: 165 patients who had undergone cardiovascular assessment and imaging were identified. The mean age was 38±13 years. Hypercholesterolaemia was present in 49.7%, hypertension in 21% and diabetes mellitus in 15.2%. Patients with these cardiovascular risk factors were older compared to those without (Table 1). Ischaemic heart disease was present in 2.4%. Cardiac structural abnormalities were present in 52 patients (31.5%) and bicuspid aortic valve was the most common abnormality (23.6%). 9.1% of patients had a history of cardiothoracic surgery or catheter intervention and 1 patient had a previous Type A aortic dissection surgically repaired. The variety and frequency of cardiac structural abnormalities are listed in Table 2. Conclusion: The prevalence of structural cardiac abnormalities and cardiovascular risk factors in Turner patients greatly exceeds that of the general population. This highlights the need for screening with cross sectional cardiac imaging plus early identification and management of cardiovascular risk factors. Funding Acknowledgement: Type of funding sources: None.